Concordancia entre las técnicas de hemaglutinación indirecta e inmunoabsorción ligado a enzimas en el diagnóstico de toxoplasmosis porcina - Gonzales L., Marlene (2019)
The aim of the present study was to determine the concordance between the indirect hemagglutination test (HAI) and the enzyme-linked immunosorbent assay (ELISA) to detect anti-Toxoplasma gondii IgG in the diagnosis of porcine toxoplasmosis. Blood samples were collected from 407 pigs in the finishing phase, from pig farms located in the coastal strip of the department of Lima, Peru. The concordance of the diagnostic techniques and the corresponding seroprevalence were evaluated using the Kappa index and the McNemar test. The results indicated that the concordance between the HAI and ELISA tests through the Kappa index was 26%, considering the regular type, with values of 18.7 ± 3.8% by the HAI method and 14.7 ± 3.4% by the method of ELISA; while no significant differences were found by the McNemar test, which could suggest that both techniques are mutually replaceable. However, it is concluded that, since the correlation is regular, it is not recommended its replacement.